Separating macrostresses from microstresses in Al2O3–15 vol%SiC particulate reinforced composites. (December 2015) - Zou, Ji; Zhong, Yuan; Zhang, Jun-Zhan; Ekelund, Magnus; Shen, Zhi-Jian
Graphical abstract: Abstract: Macrostresses and microstresses coexist in ceramics, but are difficult to distinguish. In this work, these two types of residual stresses were separated by comparing the stress levels on the mechanically and argon beam polished surfaces of Al2 O3 –15 vol%SiC particulate reinforced composites. Stresses were measured using the shift of a Raman peak of β-SiC, the shift of a luminescence line of α-Al2 O3 and a self-consistent approach. The critical grain size of SiC, over which will result in the crack formation in Al2 O3 matrix, was calculated to be 13.5–26.4 μm. New microcracking did not form in Al2 O3 grains during progressive mechanical polishing.